ChemInform Abstract: A New Bioactive Ursane‐Type Triterpenoid from Croton bonplandianum Bail. Issue 35 (8th August 2013) - Ghosh, Pranab; Mandal, Amitava; Rasul, Mohammad Golam
Abstract New triterpernoid 3α‐hydroxy‐urs‐12, 15‐diene (I) is isolated together with three known compounds.